Biopolymer engineering in food processing [ - Nicoletti-Telis, Vania Regina (Contemporary food engineering series, 2012)
"The unit operations commonly applied in food processing may affect the physicochemical and functional behavior of biopolymers and their interactions with other food compounds. Presenting an overview of their physical, physicochemical, and thermodynamic properties, this book explores the ways in which biopolymers are affected by or may affect transport processes and unit operations such as forced flow, thermal treatments, drying, and freezing- thawing. The text focuses on how such behavior can be positively applied in food products and processes design and development. It also explains the application of polysaccharides and proteins"-- Provided by publisher